2014
DOI: 10.1021/am506249r
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Mimicking Multilayer Coating on Polymeric Membrane via LbL Assembly of Cyclodextrin-Based Supramolecules

Abstract: In this study, multifunctional and heparin-mimicking star-shaped supramolecules-deposited 3D porous multilayer films with improved biocompatibility were fabricated via a layer-by-layer (LbL) self-assembly method on polymeric membrane substrates. Star-shaped heparin-mimicking polyanions (including poly(styrenesulfonate-co-sodium acrylate; Star-PSS-AANa) and poly(styrenesulfonate-co-poly(ethylene glycol)methyl ether methacrylate; Star-PSS-EGMA)) and polycations (poly(methyl chloride-quaternized 2-(dimethylamino)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…Platelet factor 4 (PF4) was used to detect platelet activation by modified biomedical materials17. Figure 6C shows the PF4 concentrations in plasma after the scaffolds contacted with blood; it could be observed that for the heparinized DLSs the PF4 concentration showed a prominent decrease compared with normal plasma or control DLS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet factor 4 (PF4) was used to detect platelet activation by modified biomedical materials17. Figure 6C shows the PF4 concentrations in plasma after the scaffolds contacted with blood; it could be observed that for the heparinized DLSs the PF4 concentration showed a prominent decrease compared with normal plasma or control DLS.…”
Section: Resultsmentioning
confidence: 99%
“…PF4 has been reported to play a vital role in platelet aggregation24, then, PF4 was used to detect platelet activation by biomedical materials17. Platelet adhesion on the scaffolds is of primary importance for blood compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…In such systems, cyclodextrins (CDs) and cyclodextrin polymers (polyCDs) can be especially used to embed hydrophobic drugs with preserved activity. PEM integrating CDs were presented in the literature for gene delivery, drug delivery, in biomaterials applications …”
Section: Introductionmentioning
confidence: 99%
“…PEM integrating CDs were presented in the literature for gene delivery, 14,15 drug delivery, [16][17][18][19][20] in biomaterials applications. [21][22][23][24][25] The effect of miscellaneous assembly parameters such as solution parameters (e.g. ionic strength, pH, temperature, polyelectrolyte concentration), or intrinsic characteristics of polyelectrolytes (molecular weight, nature, and charge density), and finally the technique used for PEM film deposition play an important role on chemical and physical properties of multilayer self-assemblies, for example film growth, thickness, film hydrophobicity, film hydration and swellability, film stability, surface morphology, and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is still a tremendous challenge to comprehensively understand the membrane-associated pathological mechanisms of these amyloidogenic diseases. Artificial biointerfaces, which mimic the membranes from the given surface properties, have been regarded as an effective complement for such research, due to their superior flexibility, tenability, and controllability [45,46]. This review presents various artificial biointerfaces, which are divided into four groups according to their special physical, chemical, or biochemical properties (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%